On the use of full polarimetric SAR data to remove azimuth ambiguity: Application ship detection - Velotto, Domenico; Lehner, Susanne (Proceedings of the European Conference on Synthetic Aperture Radar, EUSAR, 2014)
In the framework of Maritime Security and Safety, Synthetic Aperture Radar (SAR) ship detection is nowadays crucial. Nevertheless, automatic SAR ship detection is not an easy task due to the speckle and SAR artifacts that may cause false alarms. Although speckle can be reduced with proper filter algorithms or multi-looking technique, SAR artifacts are still open issues. From the ship detection point of view, those artifacts that are often generating false alarms are the azimuth ambiguity. Regarding this issue, the aim of this paper is twofold. First, the complete processing chain developed for Very High Resolution (VHS) X-band quad-pol TerraSAR-X (TS-X) data is extended to High Resolution (HR) C-band fine quad-pol Radarsat-2 (RS-2) data. Second, the proposed azimuth ambiguity removal strategy is compared to alternative methodologies existing in literature. A set of C- and X-band PolSAR data has been processed and the performances of the analyzed methods evaluated.
CRIS-Team Scopus Importer:2024-03-18